Bronchoalveolar lavage cell profiles and proteins concentrations can be used to phenotype extrinsic allergic alveolitis patients - Sterclova, Martina; Smetakova, Magdalena; Stehlik, Ludek; Skibova, Jelena; Vasakova, Martina (Multidisciplinary Respiratory Medicine, 2019)
Background: Extrinsic allergic alveolitis (EAA) patients form heterogenous group with different clinical manifestation and different prognosis. We aimed to determine how to phenotype distinct EAA subgroups. Predictive role of the bronchoalveolar lavage fluid (BALF) IL-4Rα concentration at the time of diagnosis with regard to the clinical behavior in EAA patients was studied. Methods: Concentrations of MMP-7, IL-4Rα, TNF-α, and PAR-2 were measured in the BALF od 71 EAA patients at the time of diagnosis. Lung functions and outcome data were assessed at 12 months after the diagnosis. Correlations between the BALF protein concentration, cell profile, lung functions and patient outcome were determined. Results: We found positive correlations between BALF IL-4Rα concentration and BALF eosinophils (p = 0,006), negative correlation between IL-4Rα BALF concentration and diffusing capacity (DLco) (p = 0,003), negative correlation between IL-4Rα BALF concentration and forced vital capacity (FVC) (p = 0,004) and negative correlation between IL-4Rα concentration and BALF lymphocytes (p = 0,04). The BALF concentration of IL-4Rα was significantly higher in acute exacerbation patients (p = 0,0032) and in patients progressing despite corticosteroid treatment (p = 0,04). We observed a positive correlation between MMP-7 BALF concentration and the BALF lymphocytes (p = 0.05), negative correlation between the PAR-2 BALF concentration and DLco (p = 0.04) and a negative correlation between the BALF TNF-α concentration and DLco (p = 0.03). Conclusions: Specific subgroup of EAA patients with more severe functional impact, distinct BALF cell profile and higher IL-4Rα BALF concentration can be differentiated. Correlations between the BALF concentrations of PAR-2, MMP-7 and TNF-α with clinical parameters may reflect the role of inflammation in the pathogenesis of EAA.